Pengaruh Fitur Live Shopping, Service Quality, Dan Product Quality, Terhadap Keputusan Pembelian Pada E – Commerce Tiktok Shop - Hidayat, Ahmat; Salim, Muhammad Agus; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to examine and analyze the influence of three independent variables, namely Live Shopping Features, Service Quality, and Product Quality, on the dependent variable, Purchase Decision, on the TikTok Shop E-commerce platform. This case study focuses on students of the Faculty of Economics and Business, Islamic University of Malang. Data collection was conducted through a purposive sampling method by distributing Likert scale questionnaires to 95 respondents who met the criteria. The collected data were then analyzed using multiple linear regression and hypothesis testing methods, including the F test and t-test, with the assistance of IBM SPSS version 26 software. The analysis results indicate that simultaneously, or collectively, the three independent variables, Live Shopping Features, Service Quality, and Product Quality, have a significant influence on Purchase Decisions on TikTok Shop. Live Shopping Features were found to have no significant partial effect on Purchase Decisions. Conversely, the variables Service Quality and Product Quality partially have a significant influence on Purchase Decisions. Keywords: Live Shopping Features, Service Quality, Product Quality, Purchase Decision.